Relation of Melatonin to Sleep Architecture in Children with Autism - Leu, Roberta M. (2011)
Children with autism often suffer from sleep disturbances, and compared to age-matched controls, have decreased melatonin levels, as indicated by urine levels of the primary melatonin metabolite, 6-sulfatoxymelatonin (6-SM). We therefore investigated the relationship between 6-SM levels and sleep architecture in children with autism spectrum disorders (ASD). Twenty-three children, aged 4–10 years, completed two nights of polysomnography and one overnight urine collection for measurement of urinary 6-SM excretion rate. Parents completed the Children’s Sleep Habits Questionnaire. We found that higher urinary 6-SM excretion rates were associated with increased N3 sleep, decreased N2 sleep, and decreased daytime sleepiness. The results warrant further examination to examine the effects of supplemental melatonin on sleep architecture and daytime sleepiness.